KEMAMPUAN BERPIKIR KRITIS MATEMATIS DENGAN BRAIN BASED LEARNING: SYSTEMATIC LITERATURE REVIEW - Indartiningsih, Duhwi; Nursalim, Mochamad; Rahmasari, Diana (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2023)
One of the abilities of the 21st century is the ability to think critically. Mathematical critical thinking is the ability used to solve mathematical problems using higher thinking skills, namely analyzing, synthesizing, concluding and evaluating. Brain Based Learning (BBL) is an approach that can be used to carry out learning based on brain function. The aim of this research is to describe critical mathematical thinking skills that can be improved with the BBL approach. The research was conducted using the Systematic Literature Review (SLR) method with stages: planning, implementation and reporting. The results of the study from 13 articles show that BBL can improve students' critical mathematical thinking skills.BBL is carried out in 7 stages, namely: pre-exposure; preparation; initiation and acquisition; elaboration; incubation and inserting memory; verification and confidence checking; as well as celebration and integration. Learning with the BBL approach is an alternative that can improve students' mathematical critical thinking skills, so it is recommended to use BBL on various mathematical topics and collaborate with other learning approaches or models.